Pulmonary-pleural complications of pancreatitis - L. P. Kotel’Nikova; S. A. Plaksin; P. L. Kudryavtsev; L. I. Farshatova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors investigated pulmonary-pleural complications of pancreatitis and evaluated results of CT examination in diagnostics and possibility of low invasive surgery in treatment of pancreaticogenic pleurisy. MATERIAL AND METHODS. A retrospective analysis was made of 156 medical histories of patients with acute pancreatitis and their results. An ultrasound examinations of the chest and CT scan were applied in order to determine lung tissue condition and presence of fluid in pleural cavities. RESULTS. The application of CT in diagnostics of pulmonary-pleural complications allowed doctors to identify an effusion in pleural cavities in 3,5-50 % patients with acute pancreatitis. The number and localization of effusions were defined more precisely. CONCLUSIONS. Mini-invasive procedures (puncture, videothoracoscopy) with examination of exudate on amylase activity and biopsy of pleura determined the causes of pleuritis. This was effective in pleritis elimination against a background of different methods of treatment of pancreatitis.